THE ROLE OF ELECTRONIC TRADE IN THE DEVELOPMENT OF THE DIGITAL ECONOMY - Ibadullayeva Zarnigor Ollayar kizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
It is no exaggeration to say that today the term information and communication technologies(ICT) is one of the most widely used concepts in everyday life. Because no matter what area of life we take, no matter what actions we take, we will definitely work with ICT. Indeed, in his Address to the Oliy Majlis, President Mirziyoyev noted that«we have risen7 places in the World Bank’s Doing Business ranking, ranked8th out of190 countries in terms of business registration and ranked among the best reformers». [1] they were. In recent years, the country has been implementing comprehensive reforms aimed at creating a favorable business environment for doing business, strengthening the guarantees of the rights of business entities, actively attracting foreign investment and providing full support to investors.